Geotechnical investigations and improvement of ground conditions - Patel, Anjan (Woodhead Publishing is an imprint of Elsevier, 2019)
Geotechnical Investigation and Improvement of Ground Conditions covers practical information on ground improvement and site investigation, considering rock properties and engineering geology and its relation to construction. The book covers geotechnical investigation for construction projects, including classic case studies with geotechnical significance. Additional sections cover soil compaction, soil stabilization, drainage and dewatering, grouting methods, the stone column method, geotextiles, fabrics and earth reinforcement, miscellaneous methods and tools for ground improvement, geotechnical investigation for construction projects, and forensic geotechnical engineering. Final sections present a series of site-specific case studies.
Keywords: Geotechnical engineering.; Soil mechanics.; Rock mechanics.; Building sites.; elektronické knihy; electronic books